POSISI MATA TUNAS BATANG ATAS DAN KONSENTRASI IAA TERHADAP PERTUMBUHAN GRAFTING BOUGENVILLEA SPECTABILIS DENGAN Bougenvillea variegata - Olivina S. Messakh; I Komang Sudarma (Politeknik Pertanian Negeri Kupang, 2008)
Nodes Position of Scion and IAA Concentration on Grafting Growth of Bougenvillea spectabilis And Bougenvillea variegata. The experiment aimed to examine the influence of nodes position of scion and IAA concentration on grafting process and grafting compatibility of Bougainvillea spectabilis by Bougainvillea variegata. The experiment use Factorial Randomized Block Design with five replications. The first factor was nodes position of scion (1-4, 5-8 and 9-12 from the top of branch). The result indicated that nodes position of scion influence grafting compatibility, nodes position of scion 1-4 (A1) give better influence than nodes position of scion 5-8 (A2) and 9-12 (A3). There was interaction between nodes position of scion with IAA concentration in most of parameter, except on growth and healing percentage. Combination between nodes position of scion 1-4 (A1) with IAA concentration 100 ppm (B2) is better than other combination.Key word: nodes position of scion, IAA concentration, Bougainville. Jenis data inilah yang saat ini biasanya dikemas ke dalam proyek game untuk meningkatkan efek implementasi dan menghafal informasi di tingkat bawah sadar. Sekarang ada banyak perusahaan yang sangat sukses yang mengembangkan dan mengimplementasikan alat permainan seperti friv4school dan banyak lainnya.